Screening of multi-class veterinary drugs in animal-derived food using hyphenated high-performance thin-layer chromatography techniques - Mehl, Annabel; Justus Liebig University Giessen (My University, 2022)
Rapid, efficient, cost-effective, and reliable screening methods are needed to cope with the large sample sizes in VD residue analysis to ensure food safety. Therefore, the potential of different hyphenations of HPTLC techniques for the trace-level analysis of VDs in animal-derived food was investigated. An HTpSPE method was developed for the clean-up of 66 antibiotics in muscle meat, cow milk, and chicken eggs as an alternative to routine methods for the first time. The analytes were automatically eluted via the autoTLC‒MS interface into an orbitrap-HRMS instrument for detection. The hardware and software of the autoTLC‒MS interface were improved for full automation of HPTLC‒HPLC‒MS hyphenations, and it was renamed to autoTLC‒LC‒MS interface. This improvement was the key to success in expanding the scope of the method to 81 VDs in muscle meat, cow milk, chicken eggs, and honey. The HTpSPE‒UV/vis/FLD‒HPLC‒HRMS/MS screening proved its ability to detect VD residues down to the trace level by validation. For 21 samples in parallel, the clean-up was five times faster and consumed less solvent than routine methods, and thus it will enhance current screening capacities as a more ecological option. As an alternative to MS, non-target planar bioassay screening was investigated for its potential to detect VD residues on the example of two fluoroquinolones in milk. This approach showed promising results and also revealed strong antibacterial activity outside the analytical focus. For further investigation of the observed effects, the same approach was applied to HTpSPE chromatograms of pig muscle, milk, eggs, and honey. Very prominent antibacterial zones evident in all matrices were characterized by direct coupling to HRMS. This proved fatty acids and lipids from the sample matrix to be mainly responsible for the antibacterial effect and clarified the inconsistency of positive bioassay screening results that remain unconfirmed by subsequent HPLC‒MS/MS analyses. In addition, HPTLC‒HRMS as a promising tool for the identification of unknown bioactive compounds was applied for the characterization of coral samples, Ethiopian honey, and the lipid composition in the liver of Schistosoma mansoni infected hamsters.
Keywords: High-throughput planar solid-phase extraction; Veterinary drugs; Animal-derived food; Antibacterial effects; Orbitrap-HRMS; HPLC; Antibacterial effects; Planar bioautography; Planar bioassays; HPTLC; Effect-directed detection; HPTLC-MS; TLC-HPLC-MS; Automation; autoTLC-MS interface; autoTLC-LC-MS interface; Veterinary drug residues; Fatty acids; Lipids; Bacillus subtilis assay; Aliivibrio fischeri assay; Multi-class; Residue analysis; ddc:500; ddc:540